Microinvasive pars plana vitrectomy versus panretinal photocoagulation in the treatment of severe non-proliferative diabetic retinopathy (the VIP study): study protocol for a randomised controlled trial - Xiaohu Ding; Tao Li; Lin Lu; Ling Jin; Yuan Ma; Yizhi Liu; Ying Lin; Yuqing Wu; Bingqian Liu; Shida Chen; Wenbin Zheng; Kunbei Lai; et al. (BMJ Open)
Introduction Diabetic retinopathy (DR) is the main cause of adult visual impairment worldwide. Severe non-proliferative DR (sNPDR) is an important clinical intervention stage. Currently, panretinal photocoagulation (PRP) is the standard treatment for sNPDR. However, PRP alone cannot completely prevent NPDR progression. One explanation might be that PRP does not remove the detrimental vitreous that plays an important role in DR progression. Microinvasive pars plana vitrectomy (PPV) was shown to be a safe and effective method to treat late-stage proliferative DR (PDR) by completely removing the pathological vitreous. However, whether PPV is effective in controlling sNPDR remains unknown. In this trial, we aim to compare the effectiveness of microinvasive PPV with that of PRP for sNPDR progression control.Methods and analysis This single centre, parallel group, randomised controlled trial aims to evaluate the clinical efficacy of microinvasive PPV in preventing the progression of sNPDR compared with PRP. A total of 272 adults diagnosed with sNPDR will be randomised 1:1 to the microinvasive PPV and PRP groups. The primary outcome is the disease progression rate, calculated as the rate of sNPDR progressed to PDR from baseline to 12 months after treatment. The secondary outcomes include the change in best-corrected visual acuity, re-treatment rate, diabetic macular oedema occurrence, change in central retinal thickness, change in the visual field, cataract occurrence and change in the quality of life.Ethics and dissemination The Ethics Committee of Zhongshan Ophthalmic Center approved this study (2019KYPJ108). The results will be presented at scientific meetings and submitted for publication to peer-reviewed journals.Trial registration number NCT04103671.